Clinical Characteristics and Risk Factors for Multidrug-Resistant Enterobacter cloacae Complex Bacteremia in a Chinese Tertiary Hospital: A Decade Review (2013–2022) - Han M; Hua M; Xie H; Li J; Wang Y; Shen H; Cao X (Infection and Drug Resistance)
Mei Han,1,2,* Miaomiao Hua,3,* Hui Xie,1 Jia Li,1 Yijun Wang,2,4 Han Shen,1 Xiaoli Cao1 1Department of Laboratory Medicine, Nanjing Drum Tower Hospital, the Affiliated Hospital of Nanjing University Medical School, Nanjing, Jiangsu, People’s Republic of China; 2Nanjing Field Epidemiology Training Program, Nanjing Municipal Center for Disease Control and Prevention, Nanjing, Jiangsu, People’s Republic of China; 3Department of Laboratory Medicine, The Affiliated Fuyang Hospital of Anhui Medical University, Fuyang, Anhui, People’s Republic of China; 4Nanjing Jiangning District Center for Disease Control and Prevention, Nanjing, Jiangsu, People’s Republic of China*These authors contributed equally to this workCorrespondence: Xiaoli Cao; Han Shen, Email cao-xiao-li@163.com; shenhan10366@sina.comObjective: This study aimed to analyze the antimicrobial resistance profiles, clinical characteristics and risk factors of bacteremia caused by Enterobacter cloacae complex (ECC) strains.Methods: We retrospectively collected clinical data from patients diagnosed with ECC bacteremia between 2013 and 2022 in a tertiary hospital in Jiangsu. Subgroup analyses were performed based on multidrug resistance (MDR), nosocomial acquisition, polymicrobial bacteremia, and mortality.Results: Among 188 ECC strains, the highest resistance was to ceftriaxone (39.9%), followed by ceftazidime (36.7%) and aztreonam (31.2%), with low resistance to carbapenems (< 8.6%) and amikacin (1.6%). MDR ECC accounted for 30.9% (58/188). Previous antibiotic therapy was an independent risk factor for MDR ECC (OR = 3.193, P < 0.020), while appropriate antibiotic therapy significantly reduced the risk (OR = 0.279, P < 0.001). ICU admission was an independent risk factor for polymicrobial bacteremia, both endoscopy and blood transfusion were associated with mortality.Conclusion: Carbapenems and amikacin are the most effective treatments for ECC bacteremia. Previous antibiotic therapy increases the risk of MDR ECC, while appropriate antibiotic therapy reduces it. ICU admission is an independent risk factor for polymicrobial bacteremia, both endoscopy and blood transfusion are linked to higher mortality. Effective control of MDR ECC bacteremia requires comprehensive strategies, including resistance detection, risk factor identification, and infection prevention.Keywords: Enterobacter cloacae complex, bacteremia, multidrug-resistance, clinical characteristics, risk factors